Cocreation of adaptative components for a virtual platform based on learning styles [Cocreando componentes adaptativos para una plataforma virtual basados en estilos de aprendizaje] (2019)
This paper presents the results of the co-creation stage of adaptive components for e-learning platform, focusing on learning styles. The co-creation is considered the methodology that allows to identify the adaptability requirements for virtual learning processes, within a macro project supported by research and government entities of Antioquia, which have interest in improving the education indexes of their people and have identified virtual education as a facilitator in the scope of these social purposes. © 2019 AISTI.